XORIJIY MAMLAKATLAR TAJRIBASIDA IJRO HOKIMYATINING FAOLIYATI USTIDAN PARLAMENT NAZORATI - Muhammadjonov Abrorjon Akmaljon o`g’li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2023)
This article analyzes the function of parliamentary control in evaluating the performance of the executive power of the parliament in the experience of foreign countries. Also, various models and forms of parliamentary control are covered in detail. At the same time, a comparative legal analysis of the legal bases and types of responsibility of the parliamentary control was carried out. The forms of parliamentary inquiry, deputy inquiry, interpellation, "government watch" investigative committees, vote of confidence or no confidence, parliamentary inspection are analyzed in the examples of different foreign countries.